Takotsubo syndrome in the context of the COVID-19 pandemic: An integrative review (Research, Society and Development, 2022)
Introduction: Takotsubo syndrome (TTS) is characterized by a temporary left ventricular (LV) systolic dysfunction, usually in the context of acute physical or emotional stress. Thus, the stress mechanism generated by the pandemic and the COVID-19 infection has been related to this syndrome. Objective: To analyze, through a literature review, the relationship between COVID-19 and Takotsubo Syndrome, taking into account the pathophysiological mechanisms involved. Methods: This is a literature review with searches performed in July 2022, using the PubMed database. Results and Discussion: 29 articles were selected, after full evaluation, the main findings show an increase in the incidence of TTS in the general population and in patients with COVID-19. The pathophysiological mechanisms involved include the increase in catecholamines and cortisol, cytokine storm, microvascular dysfunction and the direct action of SARS-COV-2 on cardiomyocytes and endothelium, in addition to the psychological burden resulting from the pandemic. Conclusion: The incidence of stress-induced cardiomyopathy is expected to increase in the general population, driven by the psychosocial consequences of this period. Therefore, it is imperative that clinicians are familiar with the clinical presentation, possible complications, and management of TTS.